Reliable HPLC-UV method for therapeutic levetiracetam monitoring in serum and cerebrospinal fluid of patients with epilepsy - Anna Wesołowska; Elżbieta Szczygieł-Pilut; Łukasz Hońdo; Kinga Wojewodzic; Sylwia Kozłowska; Anna Zajączkowska-Dutkiewicz; Daniel Pilut; Michał Michalski; Agnieszka Cios (Polskie Towarzystwo Farmaceutyczne, 2023)
The present study was to develop and validate a rapid analytical method of high-performance liquid chromatography with UV (HPLC/UV) detection for the determination of levetiracetam (LEV) concentration in human serum and cerebrospinal fluid (CSF) samples. The newly developed method was used to measure LEV concentration in the serum/CSF of 29 patients with different types of epilepsy; 52% (group I, n = 15) were treated with LEV in monotherapy, 48% (group II, n = 14) were co-administered with other AEDs. Serum and CSF levels of LEV were correlated with patients dosage, concomitant AEDs, therapeutic effect, and adverse drug reactions (ADRs). The calibration curves for serum and CSF were linear in the range 0.5-100 and 0.5-50 mg/L, respectively, with a coefficient correlation (R) value > 0.998 in each case. The quantitation limit was 0.5 mg/L in serum and CSF. The validated method was found to be selective, precise, and accurate. Optimal Cssmin values according to International League Against Epilepsy (12-46 mg/L) were achieved in 40 and 50% of patients in group I and II, and did not correlate with treatment efficacy in 27 and 21% patients, respectively. The ratio of serum LEV to CSF concentration (Kp) after 2 h administration LEV ranged in group I from 0.31 to 0.92 and in group II from 0.18 to 0.65. These findings indicate that the developed simple and rapid HPLC/UV method may be useful for monitoring serum/CSF LEV concentrations in patients receiving standard doses.